Integrated approach considering seasonal variability and habitat uncertainty to map habitat for the prey of South China tiger. (April 2023) - Tang, Tao; Li, Jiping; Sun, Hua; Velázquez, Javier
Graphical abstract: Highlights: Seasonal variation and uncertainties in parameterization of habitat suitability can lead to changes in habitat area and pattern of South China tiger. Minor changes in landscape area or structure may result in disparate priority patches and corridor. Assessment of priority sites based on dPCconnector index was vulnerable to the changes in landscape area and pattern. Abstract: Improving connectivity is the most commonly used approach employed in biodiversity conservation to mitigate habitat fragmentation. Graph-based networks relying on species-oriented definitions of nodes and edges are powerful tools for evaluating landscape connectivity. However, few studies have examined the effects of seasonal variation and uncertainty in parameterization of habitat suitability on the identification of priority sites. Here, a combination of the habitat suitability index, morphological spatial pattern analysis (MSPA), and graph-network analysis were combined to assess the influence of habitat variability on the identification of priority sites for reintroduction of South China tiger ( Panthera tigris amoyensis ). The combined approach was applied to the Hupingshan and Houhe National Nature Reserve and neighbourhood that are considered the most suitable places to harbour small populations of South China tigers. Six spatial or temporally static assessment scenarios for habitat suitability were used to account for uncertainties in the habitat requirement parameterizations of wild boars as the main prey for South China tigers. For each assessment scenario, three classification schemes (i.e., the P50, P70, and P90 schemes) were adopted to explain uncertainties in priority sites evaluation. In the static scenario, the minimum area of priority sites in the P50, P70, and P90 schemes was 321, 354, and 2, 371 km 2, respectively, while the areas encompassed by priority sites in the P50, P70, and P90 schemes considering the seasonal variability and habitat uncertainty were 0.2, 1.6, and 229.5 km 2, respectively. These results suggest that priority areas with high conservation value differed among the six assessment scenarios. Conservation planning of landscapes consequently should consider the impacts of changes in landscape structures caused by seasonal variation and uncertainty in the parameterization of habitat suitability for the assessment of landscape priority sites rather than relying on purely spatial or temporally static connectivity analyses.